THE PUBLIC RELATIONS STRATEGY OF PTPN IV REGIONAL 1 MEDAN IN BUILDING THE COMPANY’S CORPORATE IMAGE - Putri Sukma Nabila; Zuhriah Zuhriah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study analyses the public communication strategy of PT Perkebunan Nusantara IV (PTPN IV) Regional 1 Medan in building corporate image through Corporate Social and Environmental Responsibility (TJSL) programmes. The research employed a qualitative case study approach using interviews, observation, and documentation techniques. The findings show that PTPN IV Regional 1 implements proactive and transparent communication strategies through media relations, social media, and collaboration with the Medan City Government. One of the main programmes examined is the revitalisation of “instagrammable” bus stops as part of the TJSL initiative, which functions not only as a public facility improvement programme but also as a medium for strengthening corporate image. The study also reveals that public relations play an important role in managing public opinion, maintaining communication consistency, and building stakeholder trust. However, several challenges remain, particularly in stakeholder coordination, administrative processes, and programme implementation. Overall, the study confirms that effective public communication and social responsibility programmes contribute positively to strengthening corporate image and public trust.